EVALUATION OF PHOTOPOLYMERIZABLE HEMA-BASED HYDROGELS FOR RELEASE OF ANTI-DIABETIC DRUG METFORMIN HCL - SENOL, Sebnem (Studia Universitatis Babeș-Bolyai Chemia, 2023)
This study targets to prepare a metformin hydrochloride delivery system through the preparation and evaluation of 2-hydroxyl ethyl methacrylate (HEMA) based hydrogels. The current study explores the effect of photoinitiator (Irgacure 184, Irgacure 651), PEG-DA derivatives, 4-Acryloyl morpholine (4-AcM), and gelatine obtained by UV photopolymerization of HEMA hydrogels. Photopolymerization technique which was under UV irradiation was implemented at 365 nm and 300 s. Two different photoinitiators [2,2-Dimethoxy-2-phenyl-acetophenone (Irgacure 651)], [1-Hydroxycyclohexyl phenyl ketone (Irgacure 184)] were used to obtain the impact of photoinitiators on the metformin HCl release behavior of samples. In addition, PEG-DA Mn=258, PEG-DA Mn=700, 4-AcM, and gelatine were used to improve HEMA hydrogels. The prepared hydrogels have been characterized using Fourier transform infrared spectroscopy (FT-IR) and a digital microscope. The behaviors of hydrogels were specified by exploring swelling and release profiles in different medias. In-vitro metformin HCl release analyses have been done at pH 1.2, 6.8, and 7.4. UV-Vis spectrophotometer at 244 nm for releasing studies was used. The release results of hydrogels synthesized with Irgacure 651 demonstrated the majority quantity of the drug. Furthermore, the release amounts were higher in pH 1.2 than at previously mentioned pH medias.